Analisis Pola Kalimat Bahasa Indonesia Dalam Karangan Siswa Kelas VI SD Negeri 02 Nglegok Kecamatan Ngargoyoso Tahun Pelajaran 2014/2015 - Suwarto, Sri (2016)
The purpose of this study is : know and to describe the acquisition of indonesian sentence patterns in the composition and quality of the content in student essays sd 02 nglegok.this study is a theoretical form of practical,as the subject of action is up to 02 students nglegok whereas subject in ering action is up to 02 student essay nglegok.the data collection technique using the test methods,data analysis techniques using descriptive method that includes : (1)collect data or the result of the mastery of sentence patterns and the quality of the yable of contents (2) identify and clarify the mastery of sentence patterns indonesian (3) look for the percentage of inaccuracy in preparing sentence by sentence patterns indonesian.based on the results of the study it can be concluded that through the use of descriptive students can develop a theory about the patterns of the sentence and the terms of esay is good and can be beneficial to know,understand, and take the appropriate steps to advance the reef activities making up the student up to 02 nglegok districts ngargoyoso.